Salivary Gland Anlage Tumor in a Neonate Presenting with Respiratory Distress: Radiographic and Pathologic Correlation - Mogensen, M.A.; Lin, A.C.; Chang, K.W.; Berry, G.J.; Barnes, P.D.; Fischbein, N.J. (American Journal of Neuroradiology, 2009)
SUMMARY: We present a case of congenital salivary gland anlage tumor (SGAT) of the nasal septum in a 2-week-old infant who had difficulty breathing through her nose since birth. CT and MR imaging demonstrated a circumscribed mass within the nasal cavity that did not communicate with the intracranial compartment. Differential diagnosis and clinical significance of recognizing this rare lesion are reviewed.